Knowledge of academics and health professionals on Basic Life Support - Santos, Alan Carlos Nery dos; Petto, Jefferson; Barbosa, Ramon Martins; Moura, Renata Ferreira de; Santos, Gabriela Nery dos; Ladeia, Ana Marice Teixiera (ABCS Health Sciences, 2020)
Introduction: Inadequate assessment and lack of knowledge of the applicable procedures in emergencies are factors that can result in greater population morbidity and mortality. Objective: To systematically review studies in the national literature on the knowledge of academics and health professionals in basic life support and cardiorespiratory arrest. Methods: Systematic review of studies published in journals indexed in SciELO and LILACS databases. Search terms: “Cardiopulmonary Resuscitation”, “Basic Life Support”, “Cardiac Arrest”, “Health Education” and “Knowledge”. Complete articles published until December 2018 were included. They analyzed the knowledge of students and/or graduated health professionals about basic life support and its procedures, as well as teaching strategies. Studies with undergraduate health professionals and/or with hospital conduct and/or advanced life support were excluded. Results: Searches identified 60 articles, 16 of which were included. Of these, eleven were observational and five were intervention studies. The observational studies identified the lack of knowledge of 1,178 academics and 335 professionals about the identification of cardiorespiratory arrest, the sequence of basic life support, ventilation/compression ratio, interruption of compressions and use of the automatic external defibrillator. The intervention studies, involving 24 students and 189 professionals, indicated that active learning strategies can improve knowledge. Conclusion: Results indicate that students and graduated health professionals have limitations in their knowledge about the cardiopulmonary arrest and basic life support, which may result in great damage and short survival to emergency patients.